2013
DOI: 10.1152/ajpheart.00420.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex on the heart's metabolic and functional responses to diabetic therapies

Abstract: Lyons MR, Peterson LR, McGill JB, Herrero P, Coggan AR, Saeed IM, Recklein C, Schechtman KB, Gropler RJ. Impact of sex on the heart's metabolic and functional responses to diabetic therapies. Am J Physiol Heart Circ Physiol 305: H1584 -H1591, 2013. First published September 16, 2013 doi:10.1152/ajpheart.00420.2013.-Increased myocardial lipid delivery is a determinant of myocardial substrate metabolism and function in animal models of type 2 diabetes (T2DM). Sex also has major effects on myocardial metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
0
50
1
3
Order By: Relevance
“…In the past decade, however, studies in the human heart have demonstrated that biological sex markedly impacts cardiac metabolism at rest, 50 in response to metabolic diseases, 51,52 and in response to metabolic medications. 53 In general, women’s hearts use more FAs than men’s hearts. 52 Conversely, the hearts of men use more glucose.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…In the past decade, however, studies in the human heart have demonstrated that biological sex markedly impacts cardiac metabolism at rest, 50 in response to metabolic diseases, 51,52 and in response to metabolic medications. 53 In general, women’s hearts use more FAs than men’s hearts. 52 Conversely, the hearts of men use more glucose.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…Metformin has more beneficial effects on myocardial fatty acid and glucose metabolism in men compared with women 89. Women treated with metformin to prevent T2D in the DPP reported more adverse events than men did (15% versus 10%), and were also less adherent to treatment 90.…”
Section: Glucose-lowering Therapymentioning
confidence: 99%
“…This is consistent with prior literature, which has been fairly consistent in demonstrating that oxygen consumption is generally higher in womennormal, obese, and with type 2 diabetes mellitus, than in comparable groups of men. 10 Efficiency was also lower in lean and obese women than in their male counterparts.…”
mentioning
confidence: 83%